2014
DOI: 10.1016/j.yexcr.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress and cancer: It takes two to tango

Abstract: Problems arising during DNA replication require the activation of the ATR-CHK1 pathway to ensure the stabilization and repair of the forks, and to prevent the entry into mitosis with unreplicated genomes. Whereas the pathway is essential at the cellular level, limiting its activity is particularly detrimental for some cancer cells. Here we review the links between replication stress (RS) and cancer, which provide a rationale for the use of ATR and Chk1 inhibitors in chemotherapy. First, we describe how the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 106 publications
0
107
0
Order By: Relevance
“…While loss of p53 deregulates the cell cycle to enter S phase (5), several laboratories have demonstrated that GOF p53 accelerates cell proliferation and tumor growth in comparison promoters of genes encoding cyclin A (CCNA2), needed for origin firing (19)(20)(21), and CHK1, needed for preventing collapse of replication forks (22)(23)(24), and activates their expression in a cell cycledependent manner at the level of transcription.…”
Section: Gof P53 Mutation and Loss Of Wt P53 Hasten Time Of S Phase Ementioning
confidence: 99%
See 2 more Smart Citations
“…While loss of p53 deregulates the cell cycle to enter S phase (5), several laboratories have demonstrated that GOF p53 accelerates cell proliferation and tumor growth in comparison promoters of genes encoding cyclin A (CCNA2), needed for origin firing (19)(20)(21), and CHK1, needed for preventing collapse of replication forks (22)(23)(24), and activates their expression in a cell cycledependent manner at the level of transcription.…”
Section: Gof P53 Mutation and Loss Of Wt P53 Hasten Time Of S Phase Ementioning
confidence: 99%
“…Hyperreplicative activities of oncogenes induce cellular checkpoint responses (31,32) to prevent collapse of progressing replication forks and thus cell death (22,24,33,34). Intra-S phase CHK1 is known to protect replication forks, while inactivation of CHK1 leads to fork collapse, which could be evidenced by phosphorylation of γH2AX (22,24,33). S phase and DNA-replicating cells were identified by PI staining or BrdU pulse labeling and PI staining followed by flow cytometry.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, increased Rrm2 gene dosage significantly extends the life span of ATR mutant mice. Our study reveals the first genetic condition in mammals that reduces fragile site expression and alleviates the severity of a progeroid disease by increasing RNR activity.Supplemental material is available for this article.Received December 5, 2014; revised version accepted March 2, 2015.Replication stress (RS) has emerged as a source of genome instability in human diseases, including cancer and premature aging (Lecona and Fernandez-Capetillo 2014;Zeman and Cimprich 2014). In brief, RS is defined by the accumulation of abnormal amounts of ssDNA at stalled replication forks that, due to its recombinogenic nature, can initiate genomic rearrangements.…”
mentioning
confidence: 99%
“…Replication stress (RS) has emerged as a source of genome instability in human diseases, including cancer and premature aging (Lecona and Fernandez-Capetillo 2014;Zeman and Cimprich 2014). In brief, RS is defined by the accumulation of abnormal amounts of ssDNA at stalled replication forks that, due to its recombinogenic nature, can initiate genomic rearrangements.…”
mentioning
confidence: 99%